Woody plant encroachment constrains regeneration of ground‐layer species in a neotropical savanna from seeds. (21st February 2022) - Pinheiro, Luiz Felipe Souza; Kansbock, Leticia; Rossatto, Davi Rodrigo; Kolb, Rosana Marta
Abstract: Woody plants have been encroaching into savannas on a global scale. Global climatic changes, along with changes to disturbance regimes, are considered to be the main drivers of this process. Particularly, many formerly open physiognomies of the Brazilian savanna have become encroached by woody species over the course of a few decades under fire suppression. In this scenario, many typical savanna species of the ground‐layer are reducing their above‐ground presence, possibly due to change in environmental filtering as a result of encroachment. Consequently, at encroachment sites, changes to microhabitats occur, such as less incident light to the soil surface, reduced red:far‐red ratios and soil surface temperatures, and increased litter deposition. These changes may hinder the regenerative capacity of ground‐layer savanna species. This study investigated the role of encroachment‐induced environmental changes as filters for the recruitment ability of ground‐layer savanna species. We examined the germination and seedling emergence of 12 species under controlled conditions, simulating natural aspects of encroached and non‐encroached sites of the Brazilian savanna. The germination and/or seedling emergence of all species examined were/was negatively affected by the simulated environmental filtering changes. Increased litter deposition reduced seedling emergence more than temperature and light affected germination. Filtering changes caused by woody encroachment represent a bottleneck for the regeneration from seeds of ground‐layer savanna species. Filtering changes by woody encroachment is one of the underlying mechanism explaining changes in species presence in savannas, and it ultimately leads to positive feedback loops wherein woody encroachment begets more woody encroachment. Abstract : Abbreviated abstract summarising the article: We examined the germination responses of 12 savanna species under controlled conditions, simulating natural aspects of encroached and non‐encroached sites of a Brazilian savanna. The germination of all species examined was negatively affected by the simulated environmental filtering changes mainly by the increased litter deposition. Environmental filtering changes caused by woody encroachment represent a bottleneck for regeneration from seeds of ground‐layer savanna species.